A solar cell based on quasi-two-dimensional perovskite and a method for preparing the same

By using quasi-two-dimensional perovskite as the light absorbing layer in perovskite solar cells, the problem of poor stability of perovskite solar cells is solved, and the stability and efficiency are improved, providing prospects for the practical application of perovskite solar cells.

CN114824092BActive Publication Date: 2025-04-18BEIJING YANHE TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210428165.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-22
Publication Date
2025-04-18
Estimated Expiration
2042-04-22

AI Technical Summary

Technical Problem

The stability of perovskite solar cells is poor, making it difficult to enter practical applications.

Method used

Quasi-two-dimensional perovskite is used as the absorbing layer, and a precursor solution for Ruddlesden-Popper or Dion-Jacobson phase quasi-two-dimensional perovskite is used to obtain a high-quality perovskite film through low-pressure auxiliary treatment, and then a two-dimensional perovskite is produced by in-situ treatment by long-chain organic ammonium salt solution.

Benefits of technology

It significantly improves the stability and photoelectric conversion efficiency of perovskite solar cells, providing good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824092B_ABST
    Figure CN114824092B_ABST
Patent Text Reader

Abstract

The present invention is a solar cell based on quasi-two-dimensional-two-dimensional perovskite and a preparation method thereof. The solar cell comprises, from bottom to top, a substrate, an electron transport layer, a quasi-two-dimensional-two-dimensional perovskite active layer, a hole transport layer and a counter electrode; the quasi-two-dimensional perovskite material in the perovskite active layer is one or both of substance M and substance N; the structural formula of substance M is (A)2(B) n‑1 Pb n X 3n+1 , the structural formula of substance N is (C)(B) m‑ 1Pb m X 3m+1 ; n and m are the same or different, and the value is 1-100. The quasi-two-dimensional-two-dimensional perovskite obtained by the present invention has excellent intrinsic stability, and the stability of the solar cell prepared based on the quasi-two-dimensional-two-dimensional perovskite light-absorbing layer is significantly improved, and it has a good application prospect in the field of photovoltaic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of semiconductor optoelectronic materials and devices, and specifically, relates to a type of solar cell based on quasi-two-dimensional-two-dimensional perovskite and a preparation method thereof. Background Art

[0002] With the continuous development of globalization, traditional fossil energy is in short supply and causes irreversible damage to the environment during use. In order to meet the needs of sustainable development, the transformation from traditional fossil energy to renewable energy has become the top priority in the global energy field. For example, wind energy, solar energy, tidal energy, etc., due to the geographical limitations of other renewable energy sources such as wind energy during use, solar energy stands out as the most abundant renewable and clean energy in the world and gradually becomes the main driving force for the world's new energy transformation. There are three main forms of human use of solar energy: conversion between light energy and chemical energy (photocatalytic applications, etc.), conversion between light energy and thermal energy (solar water heaters, etc.) and conversion between light energy and electrical energy (photovoltaic industry applications, etc.). The third way, photovoltaic power generation, currently has a higher conversion efficiency and more mature application technology. Since the first solar cell was developed and manufactured by Bell Labs in 1954, solar cells have gone through three generations. The current research focus is on the third generation of new thin-film solar cells, which are divided into dye-sensitized solar cells, organic solar cells and perovskite solar cells according to the different materials of the light absorption layer. This type of optoelectronic material has not been developed for a long time, but it has aroused great interest among researchers due to its relatively simple preparation process and faster improvement in photoelectric conversion efficiency (PCE). In particular, perovskite materials show excellent optoelectronic properties including tunable band gap, high absorption coefficient, long carrier lifetime, etc., and high theoretical conversion efficiency, which makes the PCE of organic-inorganic hybrid perovskite photovoltaic devices constantly refreshed, and the current certified efficiency has reached 25.5%.

[0003] Although perovskite solar cells have a comparable photoelectric conversion efficiency to silicon-based solar cells, their stability is the biggest obstacle to their industrialization from the laboratory. Therefore, improving the intrinsic stability of perovskite solar cells and increasing the photoelectric conversion efficiency are the current research hotspots of perovskite photovoltaic devices. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the poor stability of the current perovskite battery makes it difficult to be put into practical application, and to invent a solar cell based on a quasi-two-dimensional-two-dimensional perovskite light-absorbing layer. The present invention uses a quasi-two-dimensional-two-dimensional perovskite as an active layer; in the preparation, a Ruddlesden-Popper (RP) phase quasi-two-dimensional (A) 2 (B) n-1 Pb n X 3n+1Perovskite or Dion-Jacobson (DJ) phase quasi-two-dimensional (C)(B) m-1 Pb m X 3m+1 Perovskite or (A)2(B) n- 1Pb n X 3n+1 and (C)(B) m-1 Pb m X 3m+1 The precursor solution of the mixture is prepared by low-pressure auxiliary treatment to obtain a high-quality perovskite film, and then the prepared quasi-two-dimensional perovskite is treated in situ with a long-chain organic ammonium salt solution to react in situ to generate a two-dimensional perovskite. The quasi-two-dimensional-two-dimensional perovskite obtained by the present invention has excellent intrinsic stability, and the stability of the solar cell prepared based on the quasi-two-dimensional-two-dimensional perovskite light-absorbing layer is significantly improved, which has a good application prospect in the field of photovoltaic devices.

[0005] The technical solution of the present invention is:

[0006] A solar cell based on quasi-two-dimensional-two-dimensional perovskite, which comprises, from bottom to top, a substrate, an electron transport layer, a quasi-two-dimensional-two-dimensional perovskite active layer, a hole transport layer and a counter electrode;

[0007] The quasi-two-dimensional perovskite material in the perovskite active layer is one or both of substance M and substance N; the structural formula of substance M is (A)2(B) n-1 Pb n X 3n+1 , the structural formula of substance N is (C)(B) m-1 Pb m X 3m+1 ; n and m are the same or different, and the value is 1-100, preferably 1-20;

[0008] The structural formula of the two-dimensional perovskite is preferably one of A2PbX4, A2BPb2X7, CBPbX4, and CBPb2X7;

[0009] Wherein A is an organic cation, specifically butylamine ion (BA + ), isobutylamine ion (iBA + ), dimethylamine ion (DMA + ), ethylamine ion (EA + ), mercaptoethylamine ion (ESA + ), ethanolamine ion (EOA + ), propylamine ion (PA + ), Pentylamine ion (PentA + ), phenylamine ion (PhA + ), methoxyphenylethylamine ion (MeOPEA+ ), trifluoroethylamine ion (F3EA + ), trifluoromethylaniline ion (CF3PhA + ), trifluoromethylbenzylamine ion (CF3PMA + ), pyridine methylamine ion (PyA + ), 3-dimethylamino-1-propylamine ion (3Me2PDA + ), diethylamine ion (DEA + ), benzylamine ion (PMA + ), phenethylamine ion (PEA + ), p-fluorophenylethylamine ion (pF-PEA + ), phenylpropylamine ion (PPA + ), phenylbutylamine ion (PhBA + ), 4-tert-butylbenzylamine ion (tBBA + ), 4-tert-butylanilide ion (tBPA + )

[0010] B is a cation, specifically CH3NH3 + (MA + ), NH2CH=NH2 + (FA + ), or Cs + At least one of;

[0011] The C-position cation is diaminodiphenylamine (BDAD 2+ ), p-phenylenediamine ion (PPD 2+ ), propylenediamine ion (PDAD 2+ ) Methylenediamine dihydrogen ion (MDA 2+ (CH2(NH3)2 2+ ), 2,2'-(ethylenedioxy)bis(ethylamine) ion (EDBE 2+ ), dimethylamine ion (DMA 2+ ), 3-dimethylamino-1-propylamine ion (3Me2PDA 2+ ), diethylamine ion (DEA 2+ ), ethylenediamine ion (EDAD 2+ ), 1,8-octanediamine ion (ODAD 2+ ), pentamethylenediamine ion (CH2(CH2NH2)2 2+ ), 1,6-hexanediamine ion (HDAD 2+ ), 1,2-cyclohexanediamine ion (CyHDAD 2+ ), decanediaminium ion (DDAD 2+ ), 1,4-phenylenediamine ion (PhDAD 2+), m-phenylenediamine ion (mPhDAD 2+ ), 1,4-phenylenediamine ion (PhDMAD 2+ ) containing two amino groups in one or more organic cations;

[0012] The X position is F - , Cl - Br - ,I - At least one of;

[0013] The thickness of the quasi-two-dimensional perovskite is 200-1000 nm, and the thickness of the two-dimensional perovskite is 0.5-100 nm.

[0014] The substrate is one of fluorine-doped SnO2 conductive glass (FTO), indium tin oxide transparent conductive film glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate);

[0015] The counter electrode is at least one of gold, silver, copper, aluminum and carbon.

[0016] The electron transport layer is at least one of tin dioxide (SnO2), titanium dioxide (TiO2), [6,6]-phenyl C61 butyrate methyl ester (PCBM), carbon 60 (C60), zinc oxide (ZnO), TiO2-SnO2, ZnO-TiO2, and ZnO-SnO2;

[0017] The hole transport layer is at least one of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), molybdenum trioxide, nickel oxide, cuprous iodide, cuprous thiocyanate, titanium copper, and chromium oxide.

[0018] The thickness of the electron transport layer is 1-200 nm, the thickness of the perovskite active layer is 100-1000 nm, and the thickness of the hole transport layer is 5-300 nm.

[0019] The method for preparing the quasi-two-dimensional-two-dimensional perovskite solar cell is characterized by comprising the following steps:

[0020] Step 1: Clean the transparent conductive glass substrate:

[0021] The substrate was ultrasonically cleaned with glass cleaner, deionized water and ethanol solution respectively, then dried in a nitrogen environment, and finally treated in a UV-Ozone machine for 5-60 minutes;

[0022] Step 2: Preparation of electron transport layer:

[0023] preparing an electron transport layer on a cleaned glass substrate;

[0024] Step 3: Preparation of quasi-two-dimensional perovskite layer:

[0025] Prepare a quasi-two-dimensional perovskite layer on the electron transport layer; one of the following three methods:

[0026] Method 1, the general formula is RP phase (A) 2 (B) n-1 Pb n X 3n+1 Preparation of quasi-two-dimensional perovskite: AX, BX, and PbX2 are added to a solvent according to a molar ratio of A:B:Pb:X=2:(n-1):n:(3n+1) to obtain a perovskite precursor solution with a concentration of 0.2 to 2 mol / L; the prepared perovskite precursor solution is spin-coated on an electron transport layer, and then a 200 to 1000 nm thin film is obtained by low-pressure auxiliary treatment, and then annealing is performed to form a quasi-two-dimensional perovskite layer;

[0027] Or method 2, the general formula is DJ phase (C) (B) m-1 Pb m X 3m+1 Preparation of quasi-two-dimensional perovskite: AX2, BX, and PbX2 are added to a solvent according to a molar ratio of C:B:Pb:X=1:(m-1):m:(3m+1) to obtain a perovskite precursor solution with a concentration of 0.2 to 2 mol / L; the prepared perovskite precursor solution is spin-coated on an electron transport layer, and then a 200 to 1000 nm thin film is obtained by low-pressure auxiliary treatment, and then annealing is performed to form a quasi-two-dimensional perovskite layer;

[0028] Or method three, (A)2(B) n-1 Pb n X 3n+1 and (C)(B) m-1 Pb m X 3m+1Preparation of mixed-phase quasi-two-dimensional perovskite: the precursor solutions prepared in method one and method two are mixed in a ratio of 1:0.1 to 1:10 to obtain a perovskite precursor solution with a concentration of 0.2 to 2 mol / L; the prepared perovskite precursor solution is spin-coated on the electron transport layer, and then a thin film of 200 to 1000 nm is obtained by low-pressure auxiliary treatment, and then annealing is performed to form a quasi-two-dimensional perovskite layer;

[0029] When configuring the quasi-two-dimensional perovskite precursor solution in the method one, the method two or the method three, two additives are also added to assist crystallization, one is CsPbX3, wherein X is at least one of I, Br, Cl, and F; the molar amount of the CsPbX3 is 1% to 5% of the molar amount of lead in the structural formula; the other is a chloride-containing ammonium salt (one of methylamine chloride, formamidine chloride, and phenylethylamine chloride), and the molar amount of the chloride-containing ammonium salt is 10% to 50% of the molar amount of lead in the structural formula;

[0030] The solvent in method 1, method 2 or method 3 is at least two of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), γ-butyrolactone, dimethylacetamide (DMAc), methylamine acetate, methylamine formate, methylamine butyrate and acetonitrile;

[0031] In the method 1, method 2 and method 3, the concentration of the precursor solution is calculated based on the content of Pb; the annealing time is 3s to 180min, and the annealing temperature is 50 to 400°C;

[0032] In the methods 1, 2 and 3, the rotation speed of the spin coating equipment is 2000-6000 rpm, the rotation time is 5-60 s, the ambient temperature is 1-50°C, and the relative humidity is 2%-60%. The spin coating equipment and conditions used in step 4 are the same.

[0033] Step 4: Preparation of two-dimensional perovskite layer:

[0034] A layer of amine halide / isopropanol solution is spin-coated on the surface of the quasi-two-dimensional perovskite light-absorbing layer, wherein the concentration of the amine halide / isopropanol solution is 0.1-20 mg / mL; 2 The substrate is coated with 10 to 1000 μL of the precursor solution; after coating, an annealing treatment is further performed, the annealing time is 30 seconds to 20 minutes, and the annealing temperature is 20 to 150° C.

[0035] Among them, ammonium halide salts include but are not limited to: methoxyphenethylamine iodide (MeOPEAI), 3,3-diphenylpropylamine hydroiodide (Ph2PAI), ethanolamine iodide (EOAI), mercaptoethylamine hydroiodide (ESAI), n-butyl iodide (BAI), 3-pyridinemethylamine iodide (3-PyAI), 2-thiopheneethylamine iodide (2-ThEAI), guanidine hydrochloride (GACl), trifluoroethylamine iodide (F3EAI), benzylamine chloride (PMACl), benzylamine iodide (PMAI), 4-methylphenethylamine iodide (p-MePE AI), phenethylamine iodide (PEAI), phenylpropylamine iodide (PPAI), 4-methylphenethylamine iodide (p-MePEAI), p-fluorobenzylamine iodide (pF-PMAI), 4-tert-butylbenzylamine iodide (tBBAI), 4-tert-butylaniline iodide (tBPAI), dimethylamine hydroiodide (DMAI), 3-dimethylamino-1-propylamine iodide (3Me2PDAI), diethylamine iodide (DEAI), ethylenediamine iodide (EDADI), propylenediamine iodide (PDADI), butanediamine iodide (BDADI), pentamethylenediamine iodide (CH2(CH2 NH2I)2), one or more of 1,6-hexanediamine hydroiodide (HDADI), 1,2-cyclohexanediamine iodide (CyHDADI), 1,8-octanediamine hydroiodide (ODADI), decanediamine iodide (DDADI), 2,2'-(ethylenedioxy)bisethylamine hydroiodide (EDBEI2), 1,4-phenylenediamine hydroiodide (PhDADI), m-phenylenediamine iodide (mPhDADI), and 1,4-phenylenediamine iodide (PhDMADI);

[0036] Step 5: Preparation of hole transport layer:

[0037] Spin coating a hole transport layer material solution on the two-dimensional perovskite, wherein the concentration of the hole transport layer material is 1 to 100 mg / ml;

[0038] Step 6: Prepare the counter electrode:

[0039] A metal electrode is prepared on the hole transport layer by vacuum evaporation, or a carbon electrode is prepared by blade coating.

[0040] In step 2, the electron transport layer SnO2 is prepared by a chemical bath growth method, wherein the solute of the growth solution is: 500-700 mg of urea (CO(NH2)2), 500-700 μL of hydrochloric acid (HCl), 10-15 μL of trithioglycine (TGA), and 100-200 mg of SnCl2·2H2O are added to every 50 ml of solvent deionized water. After preparation, it is refrigerated for 8-12 hours, the growth temperature is 70-100°C, and the growth time is 1-10 hours.

[0041] The quasi-two-dimensional perovskite film described in step three is prepared by a low-pressure assisted method, with a pressure of 1-500 Pa, a low-pressure treatment time of 20 to 180 s, and a temperature of 10 to 50°C.

[0042] The essential features of the present invention are:

[0043] The light-absorbing layer of the reported perovskite battery is a three-dimensional perovskite, a quasi-two-dimensional perovskite, or a three-dimensional-two-dimensional perovskite. The characteristic of the three-dimensional perovskite light-absorbing layer is that its structure is ABX3 (A is CH3NH3 + (MA + ), NH2CH=NH2 + (FA + ), or Cs + At least one of the following, B is Pb 2+ , X is 1 - ,Br - ,Cl - The characteristics of quasi-two-dimensional perovskite are the above two structures, and the characteristics of three-dimensional-two-dimensional are that the two-dimensional structure A2PbX4 or CPbX4 is generated by in-situ reaction on the surface of three-dimensional perovskite ABX3, forming ABX3-A2PbX4 or ABX3-CPbX4 three-dimensional-two-dimensional structure. However, due to the poor intrinsic stability of three-dimensional perovskite, the stability of the device is poor. Although the stability of three-dimensional-two-dimensional has been improved, it still cannot meet the requirements of commercialization. Quasi-two-dimensional perovskite can solve the stability problem of the device to a certain extent, but due to the large number of surface defects of quasi-two-dimensional perovskite, it will also affect the long-term stability of the device. At the same time, the efficiency of the battery based on quasi-two-dimensional perovskite is low, that is, quasi-two-dimensional perovskite has the limitations of relatively poor photoelectric conversion efficiency and stability.

[0044] The quasi-two-dimensional perovskite material of the present invention has a structure of RP phase quasi-two-dimensional perovskite-RP phase two-dimensional perovskite, RP phase quasi-two-dimensional perovskite-DJ phase two-dimensional perovskite, DJ phase quasi-two-dimensional perovskite-RP phase two-dimensional perovskite, DJ phase quasi-two-dimensional perovskite-DJ phase two-dimensional perovskite, specifically, RP phase quasi-two-dimensional perovskite (A) 2 (B) n-1 Pb n X 3n+1 (n is between 1 and 100)-RP phase two-dimensional perovskite (A) 2 (B) n-1 Pb n X 3n+1 (n is one of 1-5), RP phase quasi-two-dimensional perovskite (A) 2 (B) n-1 Pb n X 3n+1 (n is between 1 and 100)-DJ phase two-dimensional perovskite (C) (B) m-1 Pb mX 3m+1 (the value of m is one of 1-5), DJ phase quasi-two-dimensional perovskite (C) (B) m-1 Pb m X 3m+1 (The value of m is between 1 and 100)-RP phase two-dimensional perovskite (A) 2 (B) n-1 Pb n X 3n+1 (n is one of 1-5), DJ phase quasi-two-dimensional perovskite (C) (B) m-1 Pb m X 3m+1 (The value of m is between 1 and 100)-DJ phase two-dimensional perovskite (C) (B) m-1 Pb m X 3m+1 (The value of m is one of 1-5.) In this structure, the quasi-two-dimensional perovskite has good intrinsic stability. The two-dimensional perovskite material can significantly passivate the surface defects of the quasi-two-dimensional perovskite, reduce ion mobility, reduce non-radiative recombination losses, significantly improve the stability of the device and improve its photoelectric conversion efficiency.

[0045] The beneficial effects of the present invention are:

[0046] 1. The quasi-two-dimensional-two-dimensional perovskite material provided by the present invention has good stability. The prepared perovskite film has no obvious degradation after being placed in the air for more than 50 days, and is a preferred material for preparing perovskite solar cells;

[0047] 2. The solar cell prepared based on a quasi-two-dimensional perovskite-two-dimensional perovskite of the present invention has excellent stability, and the photoelectric conversion efficiency of the prepared device remains almost unchanged after being placed in the air for 60 days, further confirming that the quasi-two-dimensional-two-dimensional perovskite provided by the present invention is a preferred material for preparing solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a schematic structural diagram of the solar cell according to the present invention;

[0049] Figure 2 is an X-ray diffraction pattern of the quasi-two-dimensional perovskite film prepared in Example 1;

[0050] Figure 3 is an X-ray diffraction pattern of the quasi-two-dimensional-two-dimensional perovskite film prepared in Example 1;

[0051] Figure 4 is a scanning electron microscope image of the quasi-two-dimensional perovskite film prepared in Example 1;

[0052] Figure 5 is a scanning electron microscope image of the quasi-two-dimensional-two-dimensional perovskite film prepared in Example 1;

[0053] Figure 6 is the UV-visible light absorption graph of the quasi-two-dimensional-two-dimensional perovskite film prepared in Example 1;

[0054] Figure 7 The photoelectric conversion efficiency curve of the quasi-two-dimensional-two-dimensional perovskite thin film solar cell prepared in Example 1;

[0055] Figure 8 This is a stability test diagram of the quasi-two-dimensional-two-dimensional perovskite thin film solar cell prepared in Example 1;

[0056] Fig. 9 This is a graph showing the photoelectric conversion efficiency of the quasi-two-dimensional titanite thin film solar cell prepared in Comparative Example 1. DETAILED DESCRIPTION

[0057] The following embodiments can enable those skilled in the art to more fully understand the present invention, but the present invention is not limited to the scope of the embodiments.

[0058] Example 1.

[0059] Based on Quasi-Two-Dimensional (BDAD)(FA)4Pb5I 16 -2D (2-MeOPEA)2PbI4 perovskite solar cells

[0060] Based on Quasi-Two-Dimensional (BDAD)(FA)4Pb5I 16 -Two-dimensional (2-MeOPEA) 2PbI4 perovskite battery, the structural diagram of which is shown in Figure 1 As shown, from top to bottom are the gold electrode, hole transport layer, two-dimensional perovskite layer (2-MeOPEA)2PbI4, quasi-two-dimensional perovskite layer (BDAD)(FA)4Pb5I 16 , electron transport layer SnO2 and FTO conductive glass substrate, the specific preparation process is as follows:

[0061] Step 1: Clean the FTO substrate:

[0062] First, the FTO substrate was ultrasonically cleaned with glass cleaner, deionized water, and alcohol for 30 minutes respectively, and then dried with a nitrogen gun, and then ozone treated in a UV-Ozone machine for 10 minutes;

[0063] Step 2: Preparation of electron transport layer SnO2:

[0064] Weigh 625mg CO(NH2)2 and 137.5mg SnCl2.2H2O on a balance and put them into a single-mouth bottle. Then use a pipette to add 625μL HCl, 12.5μL TGA, and 50ml deionized water. Put it in a refrigerator for one day to obtain SnO2 growth solution for later use. Paste conductive glue on the opposite side of the front etching of the substrate completed by ozone, then put it in a dyeing dish, pour SnO2 growth solution to immerse the glass substrate, place it in a 90℃ oven for 4.5h, then take it out, ultrasonically clean it with deionized water for 10min, and blow it dry with a nitrogen gun; then perform annealing (annealing temperature 170℃, annealing time 60min) to obtain the transmission layer SnO2 (specific thickness is 30nm).

[0065] Step 3: Preparation of quasi-two-dimensional perovskite layer (BDAD)(FA)4Pb5I 16 :

[0066] Spin coating m=5 formamidine system perovskite precursor material (BDAD)(FA)4Pb5I on the electron transport layer 16 , (the solute molar ratio of the precursor solution is: PbI2:FAI:BDADI2=1:0.8:0.2, CsPbI3 with a molar ratio of 5% of PbI2 and methylamine chloride with a molar ratio of 30% of PbI2 are added, the solvent is a mixed solution of NMP and DMF (wherein the volume ratio of NMP and DMF is 1:9), and the concentration of lead ions in the mixed solution is 1.05mol / L), the spin coating speed is 4000r, the spin coating time is 6s, and then it is placed in a vacuum flash evaporation device for low-pressure auxiliary treatment, the pressure is 10Pa, the low-pressure treatment time is 60s, the temperature is 25℃, and finally annealing treatment is performed (annealing temperature 100℃, annealing time 20min) to obtain a quasi-two-dimensional perovskite layer (BDAD)(FA)4Pb5I 16 (Specific thickness is 350nm);

[0067] Step 4: Preparation of two-dimensional perovskite layer (2-MeOPEA) 2PbI4:

[0068] In the quasi-two-dimensional perovskite layer (BDAD)(FA)4Pb5I 16 Spin-coat the 2D perovskite precursor material 2-MeOPEAI (2-methoxyphenethylamine iodide) / isopropanol solution (the concentration of the solution is 4 mg / ml) at 4 cm 260 μL of precursor solution was dripped onto the substrate, the spin coating speed was 4000 rpm, the spin coating time was 30 s, and annealing was performed (annealing temperature was 100 ° C, annealing time was 5 min), and the upper part of the quasi-two-dimensional perovskite reacted with 2-MeOPEAI (2-methoxyphenylethyl iodinated ammonium) in situ to form a two-dimensional perovskite light-absorbing layer, thereby forming a quasi-two-dimensional-two-dimensional perovskite light-absorbing layer; (the thickness of the two-dimensional perovskite layer is about 5 nm)

[0069] Step 5: Prepare the hole transport layer Spiro:

[0070] Spin-coat the hole transport layer Spiro on the two-dimensional perovskite layer (spin-coating speed: 4000 rpm, spin-coating time: 30 s) (specific thickness: 150 nm);

[0071] Step 6: Preparation of gold electrode:

[0072] A gold electrode (with a specific thickness of 80 nm) was prepared on the hole transport layer by vacuum evaporation.

[0073] Step 5 Preparation of the hole transport layer Spiro, the solute is: 72.3 mg Spiro-OMeTAD, the solvent is: 1 ml chlorobenzene, 12.5 μL lithium bistrifluoromethanesulfonyl imide (Li-TFSI), 28 μL 4-tert-butylpyridine (TBP);

[0074] In step 6, the vacuum evaporation is performed at a vacuum degree of 5×10 -4 , the evaporation rate is 0.01-0.08nm / s.

[0075] The quasi-two-dimensional perovskite film and the quasi-two-dimensional-two-dimensional perovskite film obtained in step 4 were subjected to X-ray diffraction analysis, SEM surface morphology analysis, and absorption spectrum analysis. The X-ray diffraction results of the quasi-two-dimensional perovskite film are as follows: Figure 2 As shown in the figure, it can be seen that the prepared film has a three-dimensional perovskite diffraction peak near 14°, a quasi-two-dimensional diffraction peak of n=3 near 12.5°, and a diffraction peak of n=4 and n=5 near 15.1°. This is attributed to the fact that the size and distribution of the colloidal particles in the perovskite precursor solution are random, and different n values ​​will be formed as nucleation centers during the nucleation process. And with Figure 2 contrast, Figure 3 An obvious new diffraction peak appears near 3.8°, which is the diffraction peak of the two-dimensional perovskite, proving that the quasi-two-dimensional-two-dimensional perovskite film has been successfully prepared. The SEM results of the quasi-two-dimensional perovskite film are shown in Figure 2. Figure 4 As shown in the figure, it can be seen that the prepared film is dense and pinhole-free. Using long-chain amine salts to treat quasi-two-dimensional perovskite will react in situ to generate two-dimensional perovskite. The SEM image of the prepared quasi-two-dimensional-two-dimensional perovskite is shown in Figure 5As shown in the figure, some bright granular crystals are clearly seen on the surface of the film, which corresponds to the XRD results. It can be seen that the perovskite grains of the film are significantly enlarged, which is beneficial to reduce non-radiative coincidence losses and thus improve the efficiency of the device. The results of the absorption spectrum are shown in Figure 6 As shown in the figure, it can be seen that the prepared film has exciton absorption peaks with different n values, which corresponds to the XRD results. The photoelectric conversion efficiency curve is shown in Figure 7 As shown in the figure, it can be seen that the perovskite solar cell with quasi-two-dimensional perovskite as the light-absorbing layer achieved a photoelectric conversion efficiency of 17.36%, and the open circuit voltage, short circuit current density and fill factor were 1.09V, 22.85mA / cm 2 , and 69.3%. Stability test of quasi-two-dimensional perovskite thin film solar cells Figure 8 As shown, the prepared device was placed in an environment with a temperature of 25°C and a humidity of 20% for 60 days, and its initial efficiency was still basically unchanged, proving that the quasi-two-dimensional-two-dimensional perovskite provided by the present invention has good stability and is a preferred material for preparing solar cells.

[0076] In this embodiment Figure 7-9 The characterization is to use a solar simulator (EASISOLAR-50-3A) with a xenon lamp source to simulate sunlight to test the device's JV characteristic curve, with a calibrated light intensity of 100mW / cm 2 ,The test data was recorded by a digital source meter (K-2400). The effective area of ​​the device during the test was 0.1cm 2 ,The test delay time is 10ms.

[0077] Example 2.

[0078] Based on quasi-two-dimensional (PDAD) (FA) 5Pb6I 19 -2D (MeOPEA)2PbI4 perovskite solar cells

[0079] The other steps are the same as those in Example 1, except that:

[0080] The preparation of step 3 was changed to quasi-two-dimensional (PDAD)(FA)5Pb6I 19 Perovskite, step 4 is in quasi-two-dimensional (PDAD)(FA)5Pb6I 19 The perovskite was spin-coated with a 1 mg / ml MeOPEAI / isopropanol solution.

[0081] The MeOPEAI is methoxyphenethylamine iodide.

[0082] The quasi-two-dimensional perovskite layer described in the embodiments, wherein embodiments 1-4 are prepared by method 2, embodiments 5-8 are prepared by method 1, and embodiments 9-12 are prepared by method 3.

[0083] Example 3: Based on Quasi-Two-Dimensional (PhDAD) (FA)9Pb 10 I 31 - Solar cells based on two-dimensional (iBA) 2PbI4 perovskite

[0084] The other steps are the same as those in Example 1, except that:

[0085] The preparation of step 3 was changed to quasi-two-dimensional (PhDAD)(FA)9Pb 10 I 31 Perovskite, step 4 is changed to quasi-two-dimensional (PhDAD)(FA)9Pb 10 I 31 The perovskite was spin-coated with a 2 mg / ml iBAI / isopropanol solution.

[0086] The iBAI is isobutylammonium iodide.

[0087] Example 4: Based on Quasi-Two-Dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 - Two-dimensional (tBBA) 2PbI4 perovskite solar cells

[0088] The other steps are the same as those in Example 1, except that:

[0089] The preparation of step 3 was changed to quasi-two-dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 Perovskite, step 4 is changed to quasi-two-dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 The perovskite was spin-coated with a 0.5 mg / ml tBBAI / isopropanol solution.

[0090] The tBBAI is 4-tert-butylbenzylamine iodide.

[0091] Example 5: Based on Quasi-Two-Dimensional (BA)2(FA)4Pb5X 16 -Two-dimensional (BDAD) PbI4 perovskite solar cells

[0092] The other steps are the same as those in Example 1, except that:

[0093] The preparation of step 3 is changed to quasi-two-dimensional (BA)2(FA)4Pb5X 16Perovskite, step 4 is changed to quasi-two-dimensional (BA)2(FA)4Pb5X 16 The perovskite was spin-coated with a 1 mg / ml BDADI / isopropanol solution.

[0094] The BDADI is dibutylamine iodide.

[0095] Example 6: Based on Quasi-Two-Dimensional (MeOPEA)2(FA)5Pb6X 19 - Two-dimensional (PDAD) PbI4 perovskite solar cells

[0096] The other steps are the same as those in Example 1, except that:

[0097] The preparation of step 3 was changed to quasi-two-dimensional (MeOPEA)2(FA)5Pb6X 19 Perovskite, step 4 is changed to quasi-two-dimensional (MeOPEA)2(FA)5Pb6X 19 The perovskite was spin-coated with a 2 mg / ml PDADI / isopropanol solution.

[0098] The PDADI is propylenediamine iodide.

[0099] Example 7: Based on Quasi-Two-Dimensional (iBA)2(FA)9Pb 10 X 31 - Two-dimensional (PhDAD) PbI4 perovskite solar cells

[0100] The other steps are the same as those in Example 1, except that:

[0101] The preparation of step 3 was changed to quasi-two-dimensional (iBA)2(FA)9Pb 10 X 31 Perovskite, step 4 is changed to quasi-two-dimensional (iBA)2(FA)9Pb 10 X 31 The perovskite was spin-coated with a 3 mg / ml iBAI / isopropanol solution.

[0102] The iBAI is isobutylammonium iodide.

[0103] Example 8: Based on Quasi-Two-Dimensional (tBBA)2(FA) 19 Pb 20 X 61 -2D (mPhDMAD) PbI4 perovskite solar cell The other steps are the same as in Example 1, except that:

[0104] The preparation of step 3 was changed to quasi-two-dimensional (tBBA)2(FA) 19 Pb 20 X 61 Perovskite, step 4 is changed to quasi-two-dimensional (tBBA)2(FA)19 Pb 20 X 61 The perovskite was spin-coated with a 1 mg / ml solution of mPhDMADI in isopropanol.

[0105] The mPhDMADI is meta-phenylenediamine iodide.

[0106] Example 9: Based on Quasi-Two-Dimensional (BDAD) (FA) 4Pb5I 16 and (BA)2(FA)4Pb5X 16 Mixed-phase two-dimensional (tBBA) 2PbI4 perovskite solar cells

[0107] The other steps are the same as those in Example 1, except that:

[0108] The preparation of step 3 is changed to quasi-two-dimensional (BDAD)(FA)4Pb5I 16 and (BA)2(FA)4Pb5X 16 Mixed-phase perovskite, step 4 is changed to quasi-two-dimensional (BDAD)(FA)4Pb5I 16 and (BA)2(FA)4Pb5X 16 The mixed phase perovskite was spin-coated with a 2 mg / ml tBBAI / isopropanol solution.

[0109] The tBBAI is 4-tert-butylbenzylamine iodide.

[0110] Example 10: Based on Quasi-Two-Dimensional (MeOPEA)2(FA)5Pb6X 19 and (PDAD)(FA)5Pb6I 19 Mixed-phase two-dimensional (MeOPEA) 2PbI4 perovskite solar cells

[0111] The other steps are the same as those in Example 1, except that:

[0112] The preparation of step 3 was changed to quasi-two-dimensional (MeOPEA)2(FA)5Pb6X 19 and (PDAD)(FA)5Pb6I 19 Mixed-phase perovskite, step 4 is changed to quasi-two-dimensional (MeOPEA)2(FA)5Pb6X 19 and (PDAD)(FA)5Pb6I 19 The mixed phase perovskite was spin-coated with 1 mg / ml MeOPEAI / isopropanol solution.

[0113] The MeOPEAI is methoxyphenethylamine iodide.

[0114] Example 11: Based on Quasi-Two-Dimensional (PhDAD) (FA)9Pb 10 I31 and (iBA)2(FA)9Pb 10 X 31 Solar cells based on mixed-phase two-dimensional (PEA) 2PbI4 perovskite

[0115] The other steps are the same as those in Example 1, except that:

[0116] The preparation of step 3 was changed to quasi-two-dimensional (PhDAD)(FA)9Pb 10 I 31 and (iBA)2(FA)9Pb 10 X 31 Mixed-phase perovskite, step 4 is changed to quasi-two-dimensional (PhDAD)(FA)9Pb 10 I 31 and (iBA)2(FA)9Pb 10 X 31 The mixed phase perovskite was spin-coated with a 2 mg / ml PEAI / isopropanol solution.

[0117] The PEAI is phenethylammonium iodide.

[0118] Example 12: Based on Quasi-Two-Dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 and(tBBA)2(FA) 19 Pb 20 X 61 Mixed-phase two-dimensional (PDAD) PbI4 perovskite solar cells

[0119] The other steps are the same as those in Example 1, except that:

[0120] The preparation of step 3 was changed to quasi-two-dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 and(tBBA)2(FA) 19 Pb 20 X 61 Mixed phase perovskite, step 4 is changed to quasi-two-dimensional (3Me2PDA) (FA) 19 Pb 20 I 61 and(tBBA)2(FA) 19 Pb 20 X 61 The mixed phase perovskite was spin-coated with a 3 mg / ml PDADI / isopropanol solution.

[0121] The PDADI is propylenediamine iodide.

[0122] Comparative Example 1

[0123] Based on Quasi-Two-Dimensional (BDAD)(FA)4Pb5I 16 Perovskite solar cells

[0124] The difference from Example 1 is that there is no fourth step.

[0125] The efficiency curve of the perovskite solar cell prepared in the comparative example is shown in FIG. Fig. 9 As shown, its photoelectric conversion efficiency is 14.62%, and its open circuit voltage, short circuit current density and fill factor are 1.06V, 21.56mA / cm 2 , and 64.56%, which is significantly lower than that in Example 1 based on quasi-two-dimensional (BDAD) (FA) 4Pb5I 16 -The efficiency of solar cells based on two-dimensional 2-MeOPEAI perovskite is improved because the introduction of the two-dimensional perovskite layer effectively passivates the surface defects of the quasi-two-dimensional perovskite layer, and at the same time increases the built-in electric field of the device, which is beneficial to the transmission and separation of carriers and greatly improves the photoelectric performance of the device. In addition, since there are fewer inorganic layers between the organic layers in low-dimensional perovskites, the introduction of two-dimensional perovskites blocks the corrosion of water molecules to the quasi-two-dimensional perovskite layer, thus improving the stability of the device.

[0126] In summary, the solar cell prepared based on the quasi-two-dimensional-two-dimensional perovskite light-absorbing layer proposed in the present invention greatly improves the intrinsic stability of the perovskite solar cell and has a good application prospect in the field of photovoltaic devices.

[0127] Matters not covered by the present invention are known technologies.

Claims

1. A solar cell based on quasi-two-dimensional perovskite, characterized by The solar cell comprises, from bottom to top, a substrate, an electron transport layer, a quasi-two-dimensional-two-dimensional perovskite active layer, a hole transport layer and a counter electrode; The quasi-two-dimensional perovskite material in the perovskite active layer is one or two of substance N; the structural formula of substance N is (C)(B) m-1 Pb m X 3m+1 ; m is 1-20; The structural formula of the two-dimensional perovskite is one of A2PbX4, A2BPb2X7, CBPbX4, and CBPb2X7; Wherein A is an organic cation, specifically dimethylamine ion (DMA + ), ethylamine ion (EA + ), mercaptoethylamine ion (ESA + ), ethanolamine ion (EOA + ), propylamine ion (PA + ), butylamine ion (BA + ), isobutylamine ion (iBA + ), pentylamine ion (PentA + ), phenylamine ion (PhA + ), methoxyphenylethylamine ion (MeOPEA + ), trifluoroethylamine ion (F3EA + ), trifluoromethylaniline ion (CF3PhA + ), trifluoromethylbenzylamine ion (CF3PMA + ), pyridine methylamine ion (PyA + ), 3-dimethylamino-1-propylamine ion (3Me2PDA + ), diethylamine ion (DEA + ), benzylamine ion (PMA + ), phenethylamine ion (PEA + ), p-fluorophenylethylamine ion (pF-PEA + ), phenylpropylamine ion (PPA + ), phenylbutylamine ion (PhBA + ), 4-tert-butylbenzylamine ion (tBBA + ), 4-tert-butylanilide ion (tBPA + ) B is a cation, specifically CH3NH3 + (MA + ), NH2CH=NH2 + (FA + ), or Cs + At least one of; The C-position cation is diaminodiphenylamine (BDAD 2+ ), propylenediamine ion (PDAD 2+ ) p-phenylenediamine ion (PPD 2+ ), methylenediamine dihydrogen ion (MDA 2+ (CH2(NH3)2 2+ ), 2,2'-(ethylenedioxy)bis(ethylamine) ion (EDBE 2+ ), dimethylamine ion (DMA 2 + ), 3-dimethylamino-1-propylamine ion (3Me2PDA 2+ ), diethylammonium ion (DEA 2+ ), ethylenediamine ion (EDAD 2+ ), 1,8-octanediamine ion (ODAD 2+ ), pentamethylenediamine ion (CH2(CH2NH2)2 2+ ), 1,6-hexanediamine ion (HDAD 2+ ), 1,2-cyclohexanediamine ion (CyHDAD 2+ ), decanediaminium ion (DDAD 2+ ), 1,4-phenylenediamine ion (PhDAD 2+ ), m-phenylenediamine ion (mPhDAD 2 + ), 1,4-phenylenediamine ion (PhDMAD 2+ ) containing two amino groups in one or more organic cations; The X position is F - , Cl - Br - ,I - At least one of; The thickness of the quasi-two-dimensional perovskite is 200-1000 nm, and the thickness of the two-dimensional perovskite is 0.5-100 nm; The substrate is one of fluorine-doped SnO2 conductive glass (FTO), indium tin oxide transparent conductive film glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate); The counter electrode is at least one of gold, silver, copper, aluminum and carbon; The electron transport layer is at least one of tin dioxide (SnO2), titanium dioxide (TiO2), [6,6]-phenyl C61 butyric acid methyl ester (PCBM), carbon 60 (C60), zinc oxide (ZnO), TiO2-SnO2, ZnO-TiO2, and ZnO-SnO2; the thickness of the electron transport layer is 1-200 nm; The hole transport layer is at least one of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), molybdenum trioxide, nickel oxide, cuprous iodide, cuprous thiocyanate, titanium copper, and chromium oxide, and the thickness of the hole transport layer is 5-300 nm; The method for preparing a solar cell based on quasi-two-dimensional perovskite comprises the following steps: Step 1: Clean the transparent conductive glass substrate: The substrate was ultrasonically cleaned with glass cleaner, deionized water and ethanol solution respectively, and then dried in a nitrogen environment; Step 2: Preparation of electron transport layer: Prepare the electron transport layer on the cleaned glass substrate; finally treat it in a UV-ozone machine for 5-60 minutes; Step 3: Preparation of quasi-two-dimensional perovskite layer: A quasi-two-dimensional perovskite layer is prepared on the electron transport layer; the method is as follows: The structural formula is DJ phase (C) (B) m-1 Pb m X 3m+1 Preparation of quasi-two-dimensional perovskite: AX2, BX, and PbX2 are added to a solvent in a molar ratio of C:B:Pb:X=1:(m-1):m:(3m+1) to obtain a perovskite precursor solution with a concentration of 0.2-2 mol / L; the prepared perovskite precursor solution is spin-coated on an electron transport layer, and then a 200-1000 nm thin film is obtained by low-pressure assisted treatment, and then annealing is performed to form a quasi-two-dimensional perovskite layer; The solvent is at least two of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), γ-butyrolactone, dimethylacetamide (DMAc), methylamine acetate, methylamine formate, methylamine butyrate, and acetonitrile; Step 4: Preparation of two-dimensional perovskite layer: A layer of amine halide / isopropanol solution is spin-coated on the surface of the quasi-two-dimensional perovskite light-absorbing layer, wherein the concentration of the amine halide / isopropanol solution is 0.1-20 mg / mL; 2 The substrate is coated with 10~1000 μL of the precursor solution; after coating, it is further annealed, the annealing time is 30 s~20 min, and the annealing temperature is 20~150°C; Among them, the ammonium halide salts are: methoxyphenethylamine iodide (MeOPEAI), 3,3-diphenylpropylamine hydroiodide (Ph2PAI), ethanolamine iodide (EOAI), mercaptoethylamine hydroiodide (ESAI), butylamine iodide (BAI), isobutylamine iodide (iBAI), 3-pyridinemethylamine iodide (3-PyAI), 2-thienylethylamine iodide (2-ThEAI), guanidine hydrochloride (GACl), trifluoroethylamine iodide (F3EAI), benzylamine chloride (PMACl), benzylamine iodide (PMAI), 4-methylphenethylamine iodide (p-M ePEAI), phenethylamine iodide (PEAI), phenylpropylamine iodide (PPAI), 4-methylphenethylamine iodide (p-MePEAI), p-fluorobenzylamine iodide (pF-PMAI), 4-tert-butylbenzylamine iodide (tBBAI), 4-tert-butylaniline iodide (tBPAI), dimethylamine hydroiodide (DMAI), 3-dimethylamino-1-propylamine iodide (3Me2PDAI), diethylamine iodide (DEAI), ethylenediamine iodide (EDADI), propylenediamine iodide (PDADI), butanediamine iodide (BDADI), pentamethylenediamine iodide (CH2(CH2 NH2I)2), one or more of 1,6-hexanediamine hydroiodide (HDADI), 1,2-cyclohexanediamine iodide (CyHDADI), 1,8-octanediamine hydroiodide (ODADI), decanediamine iodide (DDADI), 2,2'-(ethylenedioxy)bisethylamine hydroiodide (EDBEI2), 1,4-phenylenediamine hydroiodide (PhDADI), m-phenylenediamine iodide (mPhDADI), and 1,4-phenylenediamine iodide (PhDMADI); Step 5: Preparation of hole transport layer: Spin coating a hole transport layer material solution on the two-dimensional perovskite, wherein the concentration of the hole transport layer material is 1-100 mg / ml; Step 6: Prepare the counter electrode: A metal electrode is prepared on the hole transport layer by vacuum evaporation, or a carbon electrode is prepared by blade coating.

2. The quasi-two-dimensional perovskite-based solar cell according to claim 1, characterized in that In the preparation method, the electron transport layer SnO2 described in step 2 is prepared by a chemical bath growth method, wherein the solute of the growth solution is: 500-700 mg of urea (CO(NH2)2), 500-700 μL of hydrochloric acid (HCl), 10-15 μL of thioglycolic acid (TGA), and 100-200 mg of SnCl2·2H2O are added to every 50 ml of solvent deionized water. After preparation, it is refrigerated for 8-12 hours, the growth temperature is 70-100°C, and the growth time is 1-10 hours.

3. The solar cell based on quasi-two-dimensional-two-dimensional perovskite according to claim 1, characterized in that In the preparation method, the quasi-two-dimensional perovskite film described in step three is prepared by a low-pressure assisted method, the pressure is 1-500 Pa, the low-pressure treatment time is 20~180 s, and the temperature is 10~50°C.

4. The solar cell based on quasi-two-dimensional-two-dimensional perovskite as described in claim 1 is characterized in that in the preparation method, the annealing time is 3 s ~180 min, and the annealing temperature is 50~400°C.

5. The quasi-two-dimensional perovskite-based solar cell according to claim 1, characterized in that In the preparation method, the rotation speed of the rotary coating equipment is 2000~6000 rpm, the rotation time is 5~60 s, the ambient temperature is 1~50°C, and the ambient relative humidity is 2%~60%.

Citation Information

Patent Citations

  • Perovskite thin film, preparation method thereof, perovskite solar cell and photoelectric device

    CN113991027A

  • Ultraviolet photoelectric detector based on two-dimensional perovskite

    CN114050218A

  • Preparation method based on quasi-two-dimensional perovskite layer and solar cell

    CN114267796A